Healthy choices in New South Wales health facilities for staff and visitors: a policy evaluation. (30th September 2020) - Trevena, H; Munn, E; King, L; Thomas, M; Shepherd, L; Cranney, L; Crino, M; O'Connell, T; Cobcroft, M
Abstract: Issue: Obesity and its determinants are risk factors for most leading causes of chronic diseases. In New South Wales (NSW), Australia, 1 in 2 adults and more than 1 in 5 children are above a healthy weight. As a key symbolic part of a suite of health eating policies, the NSW Ministry of Health implemented a Healthy Food and Drink in NSW Health facilities for Staff and Visitors Framework (Framework) across 18 Local Health Districts (LHDs). Many countries are grappling to understand the effectiveness of obesity prevention policies. Description 2: This policy evaluation synthesised evaluation study findings and internal records to assess the effectiveness of the Framework in achieving implementation targets: a) the removal of sugar-sweetened drinks (SSDs) from sale (Dec 2017), b) implementation of 12 food-based practices (Dec 2018). Results: The overall implementation package was appropriate for the large, geographically dispersed, decentralised health system (160 health facilities; 927 food outlets;76 retailers) and variable retail arrangements. The Ministry provided LHDs with overall direction, phasing, and monitoring; the LHDs had local leadership, governance, cross-functional support and autonomy to implement in a way to suit them. Accountability and pace of implementation was driven most notably by monitoring and reporting using an electronic tool (PHIMS-N), and a 'network of practice' that was pivotal to problem solving. SSDs were removed from 96% (n = 606) of applicable food outlets; overall average achievement of all practices was high at 82% (22.4 SD). Nine in 10 (92%) consumers support the Framework, and retailers are accepting of its targets. Lessons: This was the right policy at the right time, with well-orchestrated implementation. Annual monitoring and reporting enabled by PHIMS-N is unique in this type of policy implementation and essential for tracking progress, informing decision making, and ensuring accountability. Key messages: Implementation of the Framework has resulted in the removal of SSDs from sale, increased availability of healthier foods and decreased unhealthy foods as measured by 12 food-based practices. The Framework is feasible and effective in influencing retail practices in health facilities, has high consumer support for its goals, and overall acceptability and adoption amongst retailers.